1995
DOI: 10.1093/oxfordjournals.humrep.a135955
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization and early embryology: CD44 is expressed throughout pre-implantation human embryo development

Abstract: The cell surface glycoprotein CD44 has been demonstrated in a variety of cell types in embryonic and adult tissues. We have established that CD44 is present on human oocytes, cumulus cells, early embryos and pre-hatched blastocysts by indirect immunofluorescence. We have also shown that CD44 is present on 8-11 week placental stroma cells, but not on the trophoblast. These findings demonstrate that CD44 is present throughout preimplantation development, and that down-regulation occurs on the embryonic surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 0 publications
6
60
0
2
Order By: Relevance
“…A role for HA in embryo adhesion is also suggested by the observation that tumors are highly enriched with HA and that their invasiveness is correlated with HA expression [18,19]. These data and the detection of HA receptors on mammalian embryos suggest that HA plays a role in an embryo attachment, implantation, and development after being transferred to the uterine cavity [3].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A role for HA in embryo adhesion is also suggested by the observation that tumors are highly enriched with HA and that their invasiveness is correlated with HA expression [18,19]. These data and the detection of HA receptors on mammalian embryos suggest that HA plays a role in an embryo attachment, implantation, and development after being transferred to the uterine cavity [3].…”
Section: Discussionmentioning
confidence: 90%
“…By binding to receptor CD44, HA may have cellmediated activity [3]. Interestingly, human embryos possess CD44 receptors and these can be detected until the blastocyst has formed [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44 is thought to play roles in cell motility and maintenance of cell shape, and is also involved in transformation and metastasis through ERM proteins [41]. Campbell et al [11] reported qualitative CD44 expression on human preimplantation embryos. Interestingly, we consistently found murine oocytes to express the highest levels of CD44, suggesting its possible involvement in maintaining the oocyte-cumulus-cell complex.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the HCAM, CD44, although reported on human embryos [11] has not been examined in the murine embryo. Its common ligand is the extracellular matrix molecule, hyaluronate, widely expressed throughout embryonic and adult tissues.…”
Section: Introductionmentioning
confidence: 99%